Moderasi Pemahaman Hadis dalam Hukum Islam Menurut Al-Qaradhawi - Zulkifli, Rakhmawati (Lembaga Penelitian dan Pengabdian kepada Masyarakat (Center for Research and Community Services), Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2018)
This study tries to discuss the urgency of the hadith in the teachings of Islam, approaches that bring to the goals and meanings contained in the Messenger of Allah's presence and use various special methods in the philosophical foundation because the hadith is the second foundation so its role is very influential on the formation of Islamic law. Hadith thought method developed by al-Qaradhawi explaining a fair and moderate attitude or often termed middle, which distinguishes between sunnah as shari'a must be followed and sunnah is not shari'a, between general eternal and temporary. Al-Qaradhawi in some of his creation, trying to make the traditions of the Prophet can be understood in actual and contemporary manner. He did various steps, starting with describing the principles of understanding the hadith, and also explaining various factors due to errors in understanding the hadith, he also offered a moderation method in understanding the hadith, criticism of hadith and various other theories presented in his various works, even mentoring the traditions of tasyari'i and non tasyri'i so that the traditions of the Prophet can be understood in a relevant and correct manner.